Integrating Data to Measure Seriocomic Position (SEP) Among New Zealand’s Population Aged ≥65 - Exeter, Daniel J; Lee, Arier; Kerse, Ngaire; Browne, Michael (International Journal of Population Data Science, 2020)
Introduction The proportion of New Zealand’s population aged ≥65 is projected to increase significantly over the next 50 years. Many studies of health inequalities among the population ≥65 years use conventional measures of socioeconomic position (SEP), such as income, occupational class and/or educational attainment, or area-level deprivation indices, to represent the social circumstances of their population. However, there is growing consensus that these measures fail to represent the socioeconomic conditions experienced by older people. Objectives and Approach The objective of this research was to produce an index of multiple deprivation that better reflects the social conditions of New Zealand’s population aged ≥65 years. We used the Integrated Data Infrastructure (IDI) – a large research database containing microdata about people and households maintained by Statistics New Zealand – to capture socioeconomic indicators of relevance to those aged ≥65. Initially 33 person-specific indicators of SEP from routine administrative datasets including the Ministry of Social Development, Ministry of Health, Inland Revenue, the NZ Transport Association, and the 2013 Census, in addition to various spatial data providers. After quality assessment, 15 indicators were selected for our final analyses. Results In this presentation, we provide an overview of how we grouped the selected indicators into domains, weighted and combined them to create a deprivation score for individuals aged ≥65, known as the Older Person’s Index of Multiple Deprivation (OPIMD). We demonstrate associations between the OPIMD and health outcomes, comparing these to established working-age measures of SEP and deprivation. Conclusion / Implications The utility of linked administrative data for measuring socioeconomic status of the older population in New Zealand provides a tool for policy makers, researchers and agencies to develop policies and interventions that support the positive ageing of our older population.